Concepções de direito em disputa: perfis, modalidades de atuação e representações de professores do Ensino Superior no Maranhão - DOMINICI, Lorenna de Maciel (2021)
ABSTRACT In this research we exam conceptions about the ”Law” that are elaborated, transmitted and reproduced by university professors (from a University, a University Center and a Faculty) from Maranhão. These conceptions are matched to different profiles, patterns of academic careers and specializations research topics. The objective is to understand the social process of elaboration of legal doctrine (in which universities are qualified as a privileged place of production), and the current stage of professionalization of Law tutoring (since this has implications in the occupied positions and in the positions-taken by legal agents). To this end, databases were built and analyzed with information about the school path (institutions attended, year and courses taken), production (books, chapters, articles, papers at events, etc.) and university, political and cultural registrations of teachers. Afterwards, we did semi-structured interviews with representative cases of the singularities and recurrences observed, aiming to apprehend the social characteristics, professional investments and the diverse insertions behind the conceptions of law that circulate throughout the state.